(untitled) (Archives of Clinical Psychiatry, 2013)
Although there is a long tradition of philosophical and historical discussions of the mind-body problem most of them make no mention of psychic phenomena as having implications for such an issue. This article is an overview of selected writings published in the XIX and XX centuries literatures of mesmerism, spiritualism, and psychical research whose authors have discussed apparitions, telepathy, clairvoyance, out-of-body experiences and other parapsychological phenomena as evidence for the existence of a principle separate from the body and responsible for consciousness. Some writers discussed here include individuals from different time periods. Among them are John Beloff, J. C. Colquhoun, Camille Flammarion, J. H. Jung-Stilling, Frederic W. H. Myers, and J. B. Rhine. Rather than defend the validity of their position, my purpose is to document the existence of an intellectual and conceptual tradition that has been neglected by philosophers and others in their discussions of the mind-body problem and aspects of its history.